Shakespeare in love - Madden, John.; Norman, Marc.; Stoppard, Tom.; Paltrow, Gwyneth; Fiennes, Joseph; Rush, Geoffrey; Miramax Films; Universal Pictures (Firm); Bedford Falls Company (Burbank, Calif. : Miramax Home Entertainment, 1999)
When Will Shakespeare needs passionate inspiration to break a bad case of writer's block, a secret romance with beautiful Lady Viola starts the words flowing like never before.
Features: Shakespeare in love and on film, television spots, 1998 Academy Award-winning costumes, John Madden commentary track, commentary track with cast & crew, deleted scenes, Shakespeare facts, theatrical trailer, French language track.
Gwyneth Paltrow, Joseph Fiennes, Geoffrey Rush.
MPAA rating: R.
DVD, Dolby digital 5.1.
In English or French.
Closed-captioned.
Keywords: Shakespeare, William, -- 1564-1616 -- Drama; Man-woman relationships -- England -- Drama; Love -- England -- Drama; Video recordings for the hearing impaired; DVD recording